Academic Culture of Students in the Assessments of Professors of Classical Universities - E. A. Popov (Высшее образование в России)
The subject of the research in the article is the academic culture of students. In-depth interviews were conducted with professors of classical universities in Russia (N=34). The goal is to objectify the content of academic culture as a value-semantic phenomenon. The emphasis is placed on the role of academic culture in the formation of the value world of students. It is established that academic culture is an element of academism, forms social patterns. The social models include professionalism, transmission of knowledge and general cultural competencies, and others. The assessments of the state of academic culture at universities formulated by professors are summarized. In such assessments, value-semantic reflection prevails, which makes it possible to identify academic culture as a system of interaction of subjects of the educational process in order to achieve joint goals for the formation of their value world.